Politics, literature, and film in conversation essays in honor of Mary P. Nichols - Nichols, Mary P.; Dinan, Matthew D.; Taylor, Natalie; Schaeffer, Denise, 1968-; Kirkland, Paul E., 1972- (Politics, literature, & film., 2021)
"Inspired and in honor of the work of noted political theorist Mary P. Nichols, the essays in this volume explore political ideas and implications in a range of works of philosophy, literature, and film from classical antiquity to the present day, creating an interdisciplinary conversation across genres"--